Comparison of the Effects of Transcutaneous Electrical Nerve Stimulation and Low-Level Laser Therapy on Drug-Resistant Temporomandibular Disorders - Fahimeh Rezazadeh; Khadijeh Hajian; Shoaleh Shahidi; Soraya Piroozi (Shiraz University of Medical Sciences, 2017)
Statement of the Problem: Temporomandibular disorder (TMD) is a clinical term used for clinical signs and symptoms that affect the temporomandibular joints, masticatory muscles, and associated structures. Surgical and non-surgical treatments can be used for management of TMD. Non-surgical route is the main part of the treatment, since clinicians prefer non-aggressive treatment for TMD such as pharmacological and physical therapy. Low-level laser therapy (LLLT) and transcutaneous electrical nerve stimulation (TENS) are the main procedures in physical therapy. Purpose: The aim of this study was to evaluate the effectiveness of TENS and LLLT in treatment of TMD patients who did not respond to pharmacological therapy. Materials and Method: This clinical trial was performed on 45 patients who randomly received either TENS or LLLT for 8 sessions. LLLT was applied with diode laser (Ga-Al-As, 980nm, dose 5j/cm2) and TENS by using two carbon electrodes with 75 Hz frequency (0.75 msec pulse width). Helkimo index and visual analogue scale (VAS) were measured during the treatment period and throughout the follow-up sessions. Results: Significant reduction in the VAS and Helkimo index was observed in both TENS and LLLT group. There was no significant difference between the two methods during the treatment; however, TENS was more effective in pain reduction in follow-ups. Conclusion: This study justified the use of TENS therapy as well as LLLT in drug-resistant TMD. Both were useful in relieving the pain and muscles tenderness, although, TENS was more effective than LLLT.